Host and phenology shifts in the evolution of the social moth genus Thaumetopoea. - Mauro Simonato; Andrea Battisti; Carole Kerdelhué; Christian Burban; Carlos Lopez-Vaamonde; Isabelle Pivotto; Paola Salvato; Enrico Negrisolo (PLoS ONE, 2013)
The genus Thaumetopoea contains the processionary moths, a group of lepidopteran associated with forest trees, well known for the social behaviour of the larvae and for carrying urticating setae. The taxonomy of the genus is partly unresolved and a phylogenetic approach is lacking. The goal of this work is to produce a phylogeny for Thaumetopoea and to identify the main traits driving the evolution of this group. Eighteen mitochondrial and three nuclear genes were fully/partly sequenced. Markers were aligned and analysed singularly or in various combinations. Phylogenetic analyses were performed according to maximum likelihood and Bayesian inference methods. Trees obtained from largest data sets provided identical topologies that received strong statistical support. Three main clades were identified within Thaumetopoea and were further supported by several signatures located in the mitochondrial tRNAs and intergenic spacers. The reference topology was used to investigate the evolution of life history traits related to biogeography, host plant, ecology, and morphology. A multigenic approach allowed to produce a robust phylogenetic analysis of the genus Thaumetopoea, with the identification of three major clades linked to different ecological and life history traits. The first clade is associated with Angiosperm host plants and has a fast spring development of larvae on young foliage. The other clades have originated by one event of host plant shift to Gymnosperm Pinaceae, which implied a longer larval developmental time due to the lower nutritional quality of leaves. These clades showed different adaptations to such a constraint, the first with a switch of larval feeding to cold season (winter pine processionary moths), and the second with a retraction to high altitude and latitude and a development cycle extended over two years (summer pine processionary moths). Recent global warming is affecting all species and seems able to further shape the evolution of the group.